2015
DOI: 10.1080/15332640.2015.1066288
|View full text |Cite
|
Sign up to set email alerts
|

Smoking and attitudes toward smoking policy at a University in Egypt

Abstract: To assess smoking behavior, knowledge of smoking harm, and attitudes toward campus smoking policy at an Egyptian university, an online survey of students, staff, and faculty was conducted (N = 992). The smoking prevalence of 38% among men was in line with Egypt's national average, but the smoking prevalence among women of 20% was much higher than the national average. Smoking status influenced beliefs about smoking harm and attitudes toward smoking policy, with nonsmokers having stronger beliefs about the harm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 44 publications
0
7
0
1
Order By: Relevance
“…Amin et al (16) showed in 2010 that gender, age and having relatives and friends as smokers were among the major factors associated with waterpipe smoking. In other countries in the region, gender, income, living away from parents and having relatives/friends as smokers were among the risk factors for waterpipe/cigarette smoking (3,22,23,34,35). Thus, risk factors for tobacco use are shared among university students in Taibah University and other local and regional universities.…”
Section: Discussionmentioning
confidence: 99%
“…Amin et al (16) showed in 2010 that gender, age and having relatives and friends as smokers were among the major factors associated with waterpipe smoking. In other countries in the region, gender, income, living away from parents and having relatives/friends as smokers were among the risk factors for waterpipe/cigarette smoking (3,22,23,34,35). Thus, risk factors for tobacco use are shared among university students in Taibah University and other local and regional universities.…”
Section: Discussionmentioning
confidence: 99%
“…Although great effort has been made to understand the attitude and perception of students towards university tobacco control policies, little is known about the attitude of faculty and staff, the most stable population, towards such policies, especially in the Eastern Mediterranean Region. Few studies have investigated the general attitude of faculty and staff towards such policies in the region, however, none has looked for a change post policy implementation or has tested for policy effectiveness 33 , 34 . This study could set the stage for similar research in the region, thus informing future development of legislation and reducing overall tobacco consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Este resultado no solo coincide con lo registrado en todo el mundo en la población en general, en donde la prevalencia del hábito de fumar en hombres es cinco veces mayor que en las mujeres (3), sino también con otros estudios en todo el mundo que registran valores superiores de fumadores hombres (119)(120)(121)(122)(123). Sin embargo, en Europa, al igual que en esta revisión, se encuentran también, aunque escasos, estudios que presentan prevalencias superiores en mujeres.…”
Section: Discussionunclassified